Research on government subsidy strategy of biomass power supply chain considering channel encroachment - Xin Wu; Peng Liu; Jin Li; Jing Gao; Guangyin Xu; Heng Wang; Hang Ke (PLoS ONE, 2025)
To enhance the comprehensive utilization of biomass straw, governments may implement incentive policies for members of the biomass supply chain. This study examines the strategic interaction between government subsidy strategies and farmers’ channel encroachment strategies within the biomass power supply chain. A game-theoretic model is employed to analyze eight government subsidy scenarios, leading to the following conclusions: In the absence of encroachment, subsidies provided to either middlemen or farmers contribute to increased profits for the respective recipients. Notably, the analysis indicates that under the encroachment scenario, government subsidies directed solely to middlemen may negatively affect the overall social welfare of the biomass power generation supply chain. Furthermore, as channel competition intensifies, the probability and extent of this negative impact on social welfare are likely to increase. Additionally, the equilibrium outcome of the game-theoretic model establishes that farmers will invariably choose encroachment as a means to trigger government subsidies, thereby maximizing their profits. These findings provide essential theoretical insights into farmers’ strategic behavior aimed at income enhancement and offer guidance for government subsidy policies to achieve optimal social welfare.